Pengaruh Umur CEO, Struktur Dewan Komisaris, Frekuensi Rapat Komite Audit, Konsentrasi Kepemilikan, dan Tenur Audit terhadap Volatilitas Idiosinkratik - Yenny Kumalasari; Sansaloni Butar Butar (Universitas Katolik Soegijapranata Semarang, 2021)
Idiosyncratic volatility is a series of sharp increase or decreas in stock prices due to a company's fundamental. This study argues that transparent financial reports should reduce idiosyncratic volatility. Transparent financial reports are the function of CEO age, board of commissioner size, board of commissioner meetings frequency, Audit Committee meetings frequency, ownership concentration, and audit tenure. Therefore, this study examines the effect of these variables on idiosyncratic volatility. Samples were gathered from Indonesian public firms for the periode of 2014-2018. Using regression analysis for the test of hypothesis, results show that while board of commissioner meetings frequency and audit tenure have negative effects on idiosyncratic volatility, the size of the board of commissioners, concentration of ownership have positive effects on idiosyncratic volatility. On the contrary, CEO age and audit committee meetings frequency have no effects on idiosyncratic volatility.